Arrested Pneumatization of the Sphenoid: A Normal Variant Easily Mistaken for a Pathologic Entitity. (2nd September 2014) - Tummala, Neelima; Waltonen, Joshua D.; Clinger, John D.; Lack, Chris; Williams, Dan
Abstract : Objectives: (1) Describe the radiologic findings of arrested pneumatization of the sphenoid sinus. (2) Recognize this benign developmental variant to prevent unnecessary surgical intervention. Methods: A case series. Between November 2012 to January 2014, 8 subjects presented with radiologic findings consistent with arrested pneumatization of the sphenoid bone, a benign developmental variant. In each case, review of imaging by a neuroradiologist confirmed this diagnosis using strict criteria. This series includes all cases encountered during routine clinical practice during this time period. Charts were reviewed for demographic, clinical, and radiologic data. Results: In all 8 cases, arrested pneumatization of the sphenoid sinus was an incidental finding. All subjects underwent computed tomography (CT) imaging as workup for a variety of otolaryngology‐related symptoms, including headache, hearing loss, facial trauma, and sinusitis. Two patients were referred after the finding of a sphenoid lesion was mistaken for a pathologic entity. Based on CT imaging, 7 subjects were recognized as having this benign developmental variant and were managed conservatively. One patient, whose imaging revealed what appeared to be an infiltrative, midline tumor of the sphenoid sinus, underwent surgical biopsy with benign results. Upon subsequent review of CT imaging at our institution, the lesion did appear to have features consistent with arrested pneumatization. Conclusions: Considering the frequency of identification of arrested pneumatization of the sphenoid, there is a paucity of information about this diagnosis within the otolaryngology literature. Familiarity with this entity may prevent additional costly workup or unnecessary surgical intervention.